Are resource-usage patterns related to achievement? A study of an active, blended, and collaborative learning environment for undergraduate engineering courses. (4th May 2021) - Stites, Nick A.; Berger, Edward; DeBoer, Jennifer; Rhoads, Jeffrey F.
ABSTRACT: Pedagogical innovations continue to be developed and adopted in engineering education, but how these pedagogical innovations affect the students' experiences and learning outcomes is not fully understood. This study investigates the extent to which a student's resource-usage pattern relates to their course grade, scores on problem-solving exam questions, and scores on conceptual exam questions in a resource-rich undergraduate dynamics course. The regression analysis indicates that on average a student's resource-usage pattern is not predictive of their achievement, but it also identifies one individual resource-usage pattern that is associated with higher achievement and one pattern that is associated with lower achievement. Based on the resource-usage behaviours of the students exhibiting these two patterns, general resource-usage suggestions for all of the students in the course are developed. This research illustrates the power of investigating the experiences and achievements of specific subgroups of students, not just those of the stereotypical or average student.